GAMBARAN KADAR HbA1c PADA PENDERITA DIABETES MELITUS DI PUSKESMAS DUNGALIYO - Wilan Hamzah; Niluh Arwati; Mindy Eka Astuti (LPPM Universitas Bina Mandiri Gorontalo, 2023)
Diabetes Mellitus is a metabolic disorder disease marked by the increase of blood sugar due to the decreased of insulin secretion by the pancreas beta cell and insulin resistance. By measuring the glycohemoglobin (HbA1C), it can be ascertained how much the percentage of hemoglobin pigment containing glucose is. This study aimed atinvestigating the description of HbA1c levels in diabetes mellitus patients at Puskesmas Dungaliyo. It was a descriptive study with a quantitative approach. The data were primary data collected form the evaluation result on HbA1c levels in diabetes mellitus patients and secondary data collected from questionnaires and medical records of diabetes mellitus at Health Center Dungaliyo. The technique of sampling was accidental sampling by having 39 respondents as samples.. Findings revealed that out of 39 samples, 35, or 89.7% had abnormal HbA1c levels, while, the rest 4 samples or 10.3% had normal HbA1c levels. It can be recomemended that Diabetes Mellitus patients should regularly check with the docror and check in the laboratory as well as maintain a healthy life style to have good Diabetes Mellitus control.